Quantificação da biomassa e dos nutrientes em floresta de Acacia mearnsii De Wild. na região Sul do Brasil - Barichello, Leonir Rodrigues (2003)
The black wattle (Acacia mearnsii De Wild) is an originally specie of Australia that was successfully introduced in Brazil through South African seeds. The black wattle has some uses, from the bark is extracted the tannin and the wood, beyond the use for energy is used for paper and cellulose manufacturing. This study had as object the biomass and nutrients quantification obove and below ground, and analyse the ecological and silviculture implications, face to different forest harvest intensity. This study was carried out in March 2001 in a 8 years old settlement of Acacia mearnsii De Wild, from AGROSETA S.A, in Minas do Leão county, in the southeastern mountain range, has as coordinates 398979 E and 6646805 N. After the evaluation of the dendrometrics characteristics, 21 trees were selected and cut, its biomass and nutrients in the leaves, live and dead branches, bark wood, stem wood and roots were quantified. 42 samples were collected to quantify the biomass and the nutrients, and 21 trenches were opened for the determination of physics and chemistries soil analyzes. To estimate the different components of the biomass, the coefficients of the equation ln = b0 + b1 * ln d, were determined. The production of total biomass was of 132.1 Mg ha-1, allocated 2.97% in the leaves, 4.59% in the dead branches, 9.37% an the live branches, 8.28% in the bark, 62.34% in the wood and 12.45% in the roots. This total biomass contained 583.2, 18.6, 1.812,8, 458.7, 89.4, 42.3, 4.0, 0.2, 4.8, 2.9, and 0.7 kg ha-¹ of N, P, K, Ca, Mg, S, B, Cu, Fe, Mn and Zn respectively, and 54.61 Mg ha-¹ of C. The backlog of litter biomass was 27.73 Mg ha-¹, containing 472.95, 15.18, 332.52, 269.78, 32.60, 10.21, 0.74, 0.33, 23.05, 2.81, 0.99 kg ha-¹ of N, P, K, Ca, Mg, S, B, Cu, Fe, Mn and Zn respectively and 8.88 Mg ha-¹ of C. In the forest harvest, if the stem wood and the bark with more than 9 cm of diameter will be withdraw, 33.4 % of the N, 31.3% of P, 53.8% of the K, 38.3% do Ca and 42.2% of Mg will be export outwards the site. In the case of the use of wood and the bark with diameters upper to 7 cm, we will export outwards the site 38.2% of N, 36.4% of P, 60.9% of K, 43.4% of Ca and 48.8 % of Mg. If all the above ground biomass is harvested, we will export outwards the site 88.3% of N, 93.1% of P, 87.8% of K, 83.4% of Ca and 91.0% of Mg. It is essential that the harvest residues remain upon the soil, because they are an excellent source of organic matter and nutrients for the future rotations. The management system that causes the less enviromental impacts was the wood and barck harvest of the trees with a minimum diameter of 9 cm.